The Effect of Tax on Business Investment in Wakiso District. A Case Study of Kireka Along Jinja Road Highway - Divine Nassimbwa (Uganda Christian University, 2024)
The study examined the effect of tax on business investment: A case study in Kireka town along jinja road high way. It specifically focused on; the effects of tax on business investment in Kireka town, the types of taxes, the challenges associated with taxes and suggested solutions to overcome them. The study was carried out using an exploratory survey research design where qualitative research approach was also used. The data was collected using questionnaires during the data collection; simple random sampling method was used. A sample size of 52 respondents, who are business owners in Kireka town, was also used in the study. From the findings, it was revealed that taxes on business investment contribute to the financial performance of businesses. Additionally, the study revealed that the challenges of tax on business investment were; high taxes reduced on the business investment and predicting customer demand accurately is challenging, it also caused a reduction in economic growth, reduced productivity, economic freedom. The study recommended that, to promote business investment, the tax policy of Wakiso district should be fair and efficient. It should reduce the high tax burdens and simplify the tax system so that compliance costs can be reduced. More importantly, tax policies need to be predictable and stable so as to attract long-term investment.
Undergraduate research